Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2010)
Use of anterior segment optical coherence tomography to study corneal changes after collagen cross-linking Doors M, Tahzib NG, Eggink FA, Berendschot TTJM, Webers CAB, Nuijts RMMA Am J Ophthalmolol. 2009; 148: 744-51 A simple and evolutional approach proven to recanalise the nasolacrimal duct obstruction Chen D, Ge J, Wang L, Gao Q, Ma P, Li N, Li DQ, Wang Z Br J Ophthalmolol. 2009; 93: 1438-43 Macular thickness decreases with age in normal eyes: a study on the macular thickness map protocol in the Stratus OCT Eriksson U, Aim A Br J Ophthalmol. 2009; 93: 1448-52. Intravitreal injection of pegaptanib sodium for proliferative diabetic retinopathy Gonzalez V H, Giuliari G P, Banda R M, Guel D A Br J Ophthalmol. 2009; 93: 1474-8.